Pengaruh Kedalaman Tanam, Nitrogen dan Aplikasi Parakuat terhadap Pertumbuhan Eleusine Indica L. Gaertn Biotip Resisten- dan Sensitif-Parakuat - Christian Tampubolon; Edison Purba; T. Chairun Nisa B. (Universitas Sumatera Utara, 2015)
Goosegrass (Eleusine indica) is one among the weeds which is commonly found in agriculturefields and public areas. This research aims to determine the effect of burial depth of seeds onseedling emergence, nitrogen, and paraquat on the growth of paraquat-resistant(ETS) and -susceptible (EFH) biotypes of E. indica. This research was carried out in 3 experiment unitsnamely; the comparison of seedling emergence of E. indica paraquat -resistant and -susceptiblebiotypes at 5 burial depths namely 0, 2.5, 5, 7.5 , and 10 cm. Secondly, the growth response ofE. indica paraquat –resistant and –susceptible biotypes at 3 doses namely 0, 200, dan 400 kg ha-1.Thirdly, the effect of paraquat on the growth of E. indica paraquat -resistant and -susceptiblebiotypes at 7 doses namely 0, 50, 100, 200, 400, 800, 1600 g a.i. ha-1. Non factorial randomisedblock design (RBD) with three replication was used for each unit of experiment. The resultsshowed that the burial depth significantly reduced number of seedling emerged. Nitrogensignificantly increased number of tillers of ETS and EFH biotypes and dry weight of ETS biotypebut not on the dry weight of EFH of biotype, the number of panicles and seeds for ETS and EFHbiotypes. Paraquat significantly reduced the number of plant survival that survive and dry weight ofEFH biotype but it was not on the dry weight of ETS biotype.Keyword : Eleusine indica, burial depth, nitrogen, paraquat, paraquat -resistant and -susceptible